Pengaruh Strategi Green Marketing Terhadap Kepuasan dan Loyalitas Pelanggan Mcdonald’s: Study Kasus McDonald's di Kota Cirebon - Ivan Sofyan; Lili Karmela Fitriani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Research objectives 1) analyze the effect of green marketing on customer loyalty 2) analyze the effect of green marketing on customer satisfaction 3) analyze the effect of customer satisfaction on customer loyalty 4) analyze the effect of customer satisfaction in mediating green marketing with customer loyalty According to the level of explanation, this research includes relational or associative research, namely research that aims to determine the relationship between two or more variables. Retrieval of research data oriented towards McDonald's customers in Cirebon City as many as 150 customers with the minimum criteria of coming twice, being communicative and willing to have data collected. The data analysis method used is SEM-PLS analysis through the SmartPLS application. Research results: 1) green marketing has a significant positive effect on customer loyalty. 2) green marketing has a significant positive effect on customer satisfaction. 3) customer satisfaction has a significant positive effect on customer loyalty. 4) customer satisfaction can mediate in a significant positive way on the effect of green marketing on customer loyalty. Keywords: Customer Loyalty; Customer satisfaction; Green Marketing